1986
DOI: 10.1254/jjp.41.467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H2-Receptor Antagonists on Acetaminophen-lnduced Hepatic Injury

Abstract: Abstract-The effects of H2-antagonists on acetaminophen-induced hepatic injury were examined.Rats were administered acetaminophen at the dose of 800 mg/kg body, 60 hr after injection of 3-methylcholanthrene.As an H2-antagonist, cime tidine (200 mg/kg), ranitidine (50 mg or 100 mg/kg), or famotidine (20 mg or 40 mg/kg) was administered before and after acetaminophen injection. The group administered only acetaminophen had been severely damaged as evaluated by changes in serum transaminase, P-450 content, aminop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mitchell et al (10) first showed that cimetidine, a H2-receptor antagonist that is known to inhibit the mixed-function oxi dase system in liver microsomes (9), pro tected against acetaminophen-induced liver injury. Murase et al (11) also reported that cimetidine markedly reduced acetaminophen induced liver injury, while ranitidine and famotidine, other H2-receptor antagonists that do not inhibit the mixed-function oxidase system (22,24), had little or no effect. Table 4.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mitchell et al (10) first showed that cimetidine, a H2-receptor antagonist that is known to inhibit the mixed-function oxi dase system in liver microsomes (9), pro tected against acetaminophen-induced liver injury. Murase et al (11) also reported that cimetidine markedly reduced acetaminophen induced liver injury, while ranitidine and famotidine, other H2-receptor antagonists that do not inhibit the mixed-function oxidase system (22,24), had little or no effect. Table 4.…”
Section: Discussionmentioning
confidence: 98%
“…Cimetidine, which is known to inhibit the drug metabolizing activity in liver microsomes (9), has been reported to prevent acetamino phen-induced liver injury (10,11), but there have been no reports concerning the effects of the new quinolones on acetaminophen induced liver injury.…”
Section: Acceptedmentioning
confidence: 99%
See 1 more Smart Citation